2002
DOI: 10.1046/j.1365-2273.2002.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of topical nasal anaesthesia before flexible nasendoscopy: a double-blind, randomized controlled trial comparing cophenylcaine with placebo

Abstract: The objective was to evaluate the necessity to use topical nasal anaesthesia before flexible nasendoscopy and to compare its use with placebo. The study was carried out using a double-blind randomized controlled trial, with three treatment arms, at the out-patient department at Raigmore Hospital, Inverness. The participants were 90 patients attending the otolaryngology out-patient department who required flexible nasendoscopy as part of their assessment. Each participant was randomized to one of three groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
47
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 8 publications
7
47
3
Order By: Relevance
“…7 Our study has shown that using a local anaesthetic/vasoconstrictor nasal spray before performing NPL does not confer any significant benefit in reducing patient pain, discomfort or unpleasantness during the procedure. Similar results have been obtained in other trials comparing local anaesthetic sprays with a placebo spray and/or no nasal preparations 6,8,9 but in most of these studies, other confounding variables were also present, such as the use of lubricant gel and multiple examiners involved in performing the NPL.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…7 Our study has shown that using a local anaesthetic/vasoconstrictor nasal spray before performing NPL does not confer any significant benefit in reducing patient pain, discomfort or unpleasantness during the procedure. Similar results have been obtained in other trials comparing local anaesthetic sprays with a placebo spray and/or no nasal preparations 6,8,9 but in most of these studies, other confounding variables were also present, such as the use of lubricant gel and multiple examiners involved in performing the NPL.…”
Section: Discussionsupporting
confidence: 84%
“…Some other studies have also reported on the effect of local anaesthetic nasal spray on ease of examination. 9,12 In our study, a significant difference was seen with the clinician finding the examination easier in patients who received the co-phenylcaine spray. This is at odds with the results of Cain et al, where there was no significant difference in this outcome measures.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations